The embodiment of language: sign function and semiotic threshold - Diodato, Filomena (Rivista Italiana di Filosofia del Linguaggio, 2020)
In the last decades a deep revision of Saussure’s conception of language has shed some new light on the nature of language and its double essence, confirming the inadequacy of the ‘dichotomies’ by which his theory has been vulgarized, especially out of Europe. In a renewed Saussurean philosophy of language, Saussurism is no longer ascribable to an extreme culturalism, nor probably is Structuralism. Indeed, if one rethinks the dialectic between the faculté du langage, the langue and the parole, and then refocuses the notion of sign function and of semiotic threshold, Saussure’s theory and its structuralist implications could as well suggest a non-reductionist perspective that could even venture to enhance the current theories of Embodied Cognition. This paper outlines some routes by which a profitable dialogue could be opened.